Efeito da exposição aguda do inseticida Fipronil e do herbicida 2,4-D e mistura de ambos em curimbatá, Prochilodus lineatus (Teleósteo, Prochilodontidae) - Portruneli, Natália (Universidade Federal de São Carlos, 2020)
The herbicide 2,4-D and the insecticide fipronil are pesticides frequently detected in aquatic ecosystems, thus threatening wildlife and health security. The aim of the present study was to investigate the toxicity of 2,4-D (447 µg ia L-1 ) and fipronil (63.49 µg ia L-1 ), isolated and mixed in the neotropical fish Prochilodus lineatus in a time of 96 h exposure under laboratory conditions. After exposure, bioconcentration in the organism, the activities of catalase (CAT), glutathione stransferase (GST) and the level of lipid peroxidation (LPO), and changes in the surface of the branchial epithelium were determined. The bioconcentration factor was calculated at 0.17 kg-1 L for 2.4 D isolated and 12.4 kg-1 L for fipronil alone. In animals exposed to the mixture of pesticides, only fipronil bioconcentrated and the bioconcentration factor was 10.8 kg-1L. In fish exposed to 2,4-D alone, there was an increase in the enzymatic activities of CAT and GST and LPO indicating oxidative stress. In fish exposed to fipronil alone, only the GST activity increased. No change occurred in the activity of CAT and GST in animals exposed to the mixture of pesticides. In the gills, the histopathological changes occurred more intensity in fish exposed to fipronil and the mixture of pesticides. The most frequent being hypertrophy, hyperplasia, epithelial detachment, and vascular congestion. Scanning electron microscopy (SEM) analyzes showed an increase in the density of cellschloride (CC) and in the morphology of the pavement cells and CCs in fish in the group exposed to fipronil. The results showed that acute exposure to 2,4-D and fipronil induce biochemical changes in the activity of antioxidant enzymes as well as in the HAI. The exposure to fipronil increased CC density and the morphology of CC and pavement cells in the gills. The mixture of the two pesticides had antagonistic effects.
Effect of acute exposure of the insecticide Fipronil and the herbicide 2,4-D and mixture of both in curimbatá, Prochilodus lineatus (Teleósteo, Prochilodontidae)
Keywords: Cana-de-açúcar; Poluição; Peixes; Brânquias; Histopatologias; Sugarcane; Pollution; Histopathology; Synergism; Antagonism; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA